(3LhgQI GdJhMjOs - (3GdnqdnbGfj GdeUQj, CHh GdEeOGO, HQgGf GdOjf, EHQGgje Hf EHQGgje Hf MSf , (B1041 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI GdMeO ddg Ydi UdGJg Ke SdGe Gddg Ydi UdGJg (B- (3Ydi HHj LGA HGdJhMjOj hbO YQi GdOjf Yf GdJhMjOjs
(3BNQgG (B:s
(3ef GdQLje Ke faSj hGdghi hef jed dghdGj bO Zhi (B- (3gPG hCQLh Gddg Gf jefMfG YfO GdSDGd eWdbG MLJfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 28s
(3eYLe GdeDdajf (B1 / 8s
(3cTa GdXfhf (B1 / 620s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds